Adaptive PID controller with auto-tuning applied to the agricultural food industry - Figueroa, AAP (2017)
After being aware of the high demand of vapor compression refrigeration systems for the conservation of agri-food and hydrobiological products and the high economic costs that the use of these systems produces, both academia and industry have carried out studies that have allowed them to develop advanced technologies in order to produce savings in energy consumption. These advances lie in the production of new control algorithms to be implemented in the domestic as well as the industrial, and for the case of the academy, for tests in pilot plants. This document explains the design of a control system based on the algorithm of an adaptive PID autotunning that has a learning process, which, to demonstrate a better performance of the systems of cooling by compression of steam and, in addition, the controller must avoid compressor starts, during which there is a lot of energy consumption. In addition, the construction of the mathematical model used to express the dynamics of a conventional refrigeration system used in product preservation processes in the agro-food industry is presented.